Pengaruh Konseling Terhadap Tingkat Kepatuhan Konsumsi Suplemen Tambah Darah Pada Kejadian Anemia Ibu Hamil Di Klinik Utama Duta Rahayu Sidareja - Adi Susanto; Amelia Resti Fauzi (Prosiding Seminar Nasional Ilmu Kesehatan dan Keperawatan, 2024)
Anemia is the most common and potentially serious public health problem in the world, the vulnerable groups are women of childbearing age and pregnant women. Anemia in pregnancy is defined as a hemoglobin level of less than 11 g/ dL due to the inability of the tissues to produce erythrocytes (erytropoetic) to maintain normal Hb. This research aimed to find out the effect of counseling on the level of adherence to blood suplement consumption in anemia of pregnant women. This research was conducted at Duta Rahayu Sidareja Main Clinic. This research used quasi-experimental with a population of 122 respondents divided into two groups with 61 respondents as the treatment group and 61 respondents as the control group. The data analysis used the Independent t- test. The results of this reserach showed a p value of 0.000 with a significance limit of <0.05. The conclusion is that this research has the influence of the counseling provided with brochure media. Suggestions for pregnant women to adhere to consuming blood- boosting supplements during pregnancy to prevent anemia.